Application of immobilized TiO2 photocatalysis to improve the inactivation of Heterosigma akashiwo in ballast water by intense pulsed light. (April 2015) - Feng, Daolun; Xu, Shihong; Liu, Gang
Highlights: TiO2 photocatalysis is firstly incorporated into pulse intense light inactivation. Here pulse intense light/TiO2 photocatalysis obtains 40.15% elevation in inactivation. Here pulse intense light/TiO2 photocatalysis saves 35.71% energy consumption. Pulse intense light/TiO2 shows the potential for applying in ballast water treatment. Abstract: Ballast water exotic discharge has been identified as a leading vector for marine species invasion. Here immobilized TiO2 photocatalysis is introduced to improve the performance of intense pulsed light. For intense pulsed light/TiO2 photocatalysis, a typical inactivation of 99.89 ± 0.46% can be achieved under treatment condition of 1.78 L min −1 flow rate, 300 V pulse peak voltage, 15 Hz pulse frequency and 5 ms pulse width. Moreover, within tested 220–260 V peak voltage, 18.37–40.51% elevation in inactivation is observed in comparison with intense pulsed light treatment alone. The rough energy consumption of the tested intense pulsed light/TiO2 treatment system is about 1.51–2.51 times higher than that of the typical commercial UV ballast water treatment system. The stability of the photocatalytic reactivity and intactness of loaded TiO2 film is proved within 20-d's test, while local erosion on stainless steel support is observed after 30-d's test. The results indicate that intense pulsed light/TiO2 photocatalysis is likely to be a competitive ballast water treatment technique, while further measures is needed to reduce the energy consumption and ensure the performance of TiO2 film in a long run.